Effect of Age Hardening on Phase Composition and Microhardness of V-Free and V-Alloyed High-Nitrogen Austenitic Steels; AIP Conference Proceedings; Vol. 2051 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2018 (AMHS’18) - Maier G. Galina; Astafurova E. Elena; Moskvina V. Valentina; Melnikov E. Eugene; Astafurov S. Sergey; Tumbusova I. Irina; Fortuna A. Anastasia; Panchenko M. Marina; Mironov Yu. Yuri; Mirovoy Yu. Yuri; Galchenko N. Nina (2018, 2018)
Title screen